Penerapan Metode Waterfall Pada Sistem Informasi Akademik Sekolah Menengah Kejuruan - Veti Apriana (LPPM Universitas Bina Sarana Informatika, 2022)
Abstract - Good information is actually information that can be comprehensive or reach all interested parties to be able to know and be clear about the information. Information technology has supported various fields of life including in the economic field, education, entertainment and other fields. The users of information technology at this time have covered almost all ages, both children, adults and parents. In the field of education itself, technological developments are used in disseminating information, data processing is still carried out in the conventional way, often making it difficult to search for data, besides that it requires more space and time. Dissemination of web-based information is certainly very easy to access data, especially for the parties concerned. This study aims to produce an Academic Information System which is expected to be able to overcome the weaknesses of the current system in Vocational High Schools. The method used is the waterfall method with the stages starting with needs analysis, design, code generation, testing and support with the final result in the form of a web-based academic information system that is expected to be able to record data, process data into quality information.